2009
DOI: 10.1590/s0100-06832009000200011
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production and phosphorus use of forage grasses fertilized with two phosphorus sources

Abstract: SUMMARYA major constraint to agricultural production in acid soils of tropical regions is the low soil P availability, due to the high adsorption capacity, low P level in the source material and low efficiency of P uptake and use by most of the modern varieties grown commercially. This study was carried out to evaluate the biomass production and P use by forage grasses on two soils fertilized with two P sources of different solubility. Two experiments were carried out, one for each soil (Cambisol and Latosol),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 13 publications
0
16
0
11
Order By: Relevance
“…Gargantini et al (1963), Yorinori (2003) (Fernandes et al, 2010) e a translocação para os tubérculos proporcionaram diminuição na quantidade de N, P, K, Mg e S acumulada nas folhas de todas as cultivares na fase final do ciclo (Figuras 2d, 3d, 4d, 6d e 7d). Já a redução na quantidade de Ca acumulada nas folhas na fase final do ciclo ocorreu, principalmente, devido à senescência e queda de folhas (Fernandes et al, 2010), uma vez que o Ca apresenta baixa capacidade de redistribuição nos tecidos (Figura 5d), e o teor foliar desse nutriente aumentou (Fernandes et al, 2010), pois o acúmulo de nutrientes é dependente do teor de nutrientes nos tecidos e da produção de MS (Ramos et al, 2009). Na fase final do ciclo, a cultivar Asterix apresentou o maior acúmulo de N e Mg nos tubérculos, o que é resultado do maior acúmulo de MS (Fernandes et al, 2010) e do elevado valor e período de duração das taxas de acúmulo desses nutrientes nos tubérculos dessa cultivar (Figuras 2e e 6e e Quadro 2).…”
Section: Resultsunclassified
“…Gargantini et al (1963), Yorinori (2003) (Fernandes et al, 2010) e a translocação para os tubérculos proporcionaram diminuição na quantidade de N, P, K, Mg e S acumulada nas folhas de todas as cultivares na fase final do ciclo (Figuras 2d, 3d, 4d, 6d e 7d). Já a redução na quantidade de Ca acumulada nas folhas na fase final do ciclo ocorreu, principalmente, devido à senescência e queda de folhas (Fernandes et al, 2010), uma vez que o Ca apresenta baixa capacidade de redistribuição nos tecidos (Figura 5d), e o teor foliar desse nutriente aumentou (Fernandes et al, 2010), pois o acúmulo de nutrientes é dependente do teor de nutrientes nos tecidos e da produção de MS (Ramos et al, 2009). Na fase final do ciclo, a cultivar Asterix apresentou o maior acúmulo de N e Mg nos tubérculos, o que é resultado do maior acúmulo de MS (Fernandes et al, 2010) e do elevado valor e período de duração das taxas de acúmulo desses nutrientes nos tubérculos dessa cultivar (Figuras 2e e 6e e Quadro 2).…”
Section: Resultsunclassified
“…Dias et al (2015) evaluating the production of Piatã grass submitted to different sources of phosphorus report that the Piatã grass was responsive to phosphate fertilization when compared to the control. Ramos et al (2009) also observed that plants from the genus Brachiaria were more efficient in absorbing P from low solubility sources compared with forage sorghum.…”
Section: Discussionmentioning
confidence: 84%
“…The lowest accumulation of P contents in the tissue of plants fertilized with SS and TS may be attributed to the diluting effect of this nutrient, as it achieved the highest biomass production. The high solubility of these phosphate fertilizers is responsible for the release of phosphate ions into the soil more quickly, resulting in immediate gains in crop productivity in relation to BRPs (Scholefield et al, 1999;Ramos et al, 2009). However, over many years, the effect of BRPs may be similar (Resende et al, 2006) or even higher (Scholefield et al, 1999) than soluble phosphates due to their higher residual effect.…”
Section: Discussionmentioning
confidence: 99%
“…Estima-se que aproximadamente 75 % do P aplicado seja sorvido nas partículas de solo (Raij, 2004), resultando numa eficiência agronômica inferior a 20 % (Araújo et al, 2003;Ramos et al, 2009). Em razão disso, há necessidade de aplicações frequentes de fertilizantes fosfatados para proporcionar e manter alta produtividade.…”
Section: Introductionunclassified
“…Devido à alta solubilidade, os fosfatos acidulados liberam íons fosfato ao solo de forma mais rápida e intensa e apresentam maior efeito imediato na produtividade das culturas em comparação aos FN (Scholefield et al, 1999;Ramos et al, 2009). Entretanto, algumas vezes, ao longo de diversos anos o efeito dos FN pode ser similar (Resende et al, 2006) ou até mesmo superior (Braga et al, 1991;Scholefield et al, 1999) ao dos fosfatos solúveis, devido ao seu maior efeito residual.…”
Section: Introductionunclassified